Gender Subordination in Ni Komang Ariani's Collection Short Stories of ‘Bukan Permaisuri’ - Sumarni; Suta Wardianto, Bayu; Kurniawan, Heru (International Proceedings of Nusantara Raya, 2022)
Gender sebordination is a condition of injustice experienced by a particular gender that is manifestly invisible but can be felt. This study aims to describe gender subordination in the collection of short stories ‘Bukan Permaisuri’ by Ni Komang Ariani. This research uses qualitative research methods. The data in the study were analyzed using content analysis techniques, data collection applying library techniques, listening techniques, and note-taking techniques. This study uses the validity of data involving related experts so that research data is more guaranteed and objective. The results and findings of this study are that there are three forms of gender subordination, including: including (1) physical subordination, (2) psychological subordination, (3) social subordination. The gender subordination that occurs in the perempuam figures in the collection of short stories that are treated by not considering them important and not calculated in people's lives.